Online dropship for business transaction in Malaysia: views from Muslim scholars - Jahari, Nor Azah; Al-Aidaros, Al-Hasan (Islamic Business School, 2016)
Nowadays, people are not only buying things in a traditional way but the advancement of technology has evolved and people buy products through online transaction.In Malaysia, the phenomenon of buying through online dropship agent becomes one of the popular ways of buying products.However, questions arise whether the transaction is in accordance to Shariah (Islamic Law) or the other way around. In practice, the dropship transaction uses agent as the seller of the product; where in fact the agent does not hold the product.The two important issues raised are the transaction itself whether it is considered as lawful or not; and the issue of uncertainty (Gharar). This study aims to explain the online dropship transaction from an Islamic perspective.Among the topics addressed in this paper are Gharar issues, transaction between the dropship agent, customer, and postage issues. Open ended questions were given to Muslim scholars in Malaysia and one interview with the dropship agent was conducted to support the findings.The results of this study show that the dropship transaction is considered valid from Islamic perspective as long as it is based on Bai as-salam concept.As the Shariah is being followed by both parties (dropship agent and buyer), than they will get the potential benefits from the business transaction because it makes them feel ease and satisfaction in conducting online business.